Partnerships norms and childlessness in Hungary and Transylvania in European view - Szalma Ivett (Belvedere Meridionale, 2016)
This paper provides an overview of female childlessness and partnerships in Europe by using European Values Study – an international survey. Furthermore it focuses on Hungary and Transylvania more deeply based on interview analysis in these two societies. According to our fi ndings, fundamental changes are currently in progress in Europe and the correlation of childbearing and the changes of relationships is going to be weaker and weaker. We found that childless women in Hungary are more tolerant towards childbearing by single mothers than their Transylvanian peers who are more emphasized the dimension of selfi shness and the lack of a father model related to single motherhood. As for having children in same-sex partnership there are diff erent attitudes: in northern and western countries were more liberal than in the southern or eastern countries. Th e interviews revealed that this issue has strong connection with traditional attitudes regarding families.